Leadership for systems change: Researcher practices for enhancing research impact in the prevention of chronic disease - Pescud, Melanie; Rychetnik, Lucie; Allender, Steven; Irving, Michelle J.; Howse, Eloise; Rutter, Harry; Ison, Ray; Riley, Therese; Friel, Sharon; Finegood, Diane T. (Frontiers in Public Health, 2022)
Strengthening systems for chronic disease prevention is essential. Leadership for systems change is an important key to strengthening systems. Leadership in prevention research for supporting systems change remains a relatively abstract concept and there is limited empirical information about the leadership practices of prevention research teams when viewed through a complexity lens. In this paper we examine and describe some systems leadership practices for creating change through prevention research, as identified in a series of six case studies. A qualitative approach incorporating semi-structured interviews, participant observation, and document review was used to facilitate an in-depth investigation of the research topic. Several researcher practices for enhancing research impact in the prevention of chronic disease were distilled from the data pertaining to how they sought to create change. These included persuasive communication, compassion and deep listening, reflective practice, and embedding themselves within the systems they sought to change. The findings provide insights that may assist prevention researchers and other practitioners dedicated to creating change in chronic disease prevention.